The archaeological landscape of Machuchoquequirao, Tambillo and Inkiltambo in the Cachimayo microbasin, Cusco-Peru - Cama Ttito, Percy Alfredo (2024)
This research was developed from a post-processual archaeological perspective, taking into account the methodological and theoretical contributions of Criado and Hodder. The analysis was established in the different dimensions (physical, social and symbolic) following the guidelines of landscape archeology; Through formal analysis, the shapes of the space were established and the built space was identified in its entirety. In addition, it made it possible to identify different geomorphological units, recognize its surface, characteristics, limits and predefine its potential uses. In this way, virtual reconstruction and deconstruction can be achieved to understand the meaning of space.